2017
DOI: 10.1249/mss.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mental Fatigue on Endurance Performance in the Heat

Abstract: Purpose: Mental fatigue is a psychobiological state caused by prolonged periods of demanding cognitive activity and has been observed to decrease time-trial (TT) endurance performance by ~3,5% in normal ambient temperatures. Recently it has been suggested that heat may augment the negative effect of mental fatigue on cognitive performance, raising the question whether it may also amplify the effect of mental fatigue on TT-performance. Methods: In 30 °C and 30% relative humidity, ten endurance-trained male athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 40 publications
(100 reference statements)
2
54
0
Order By: Relevance
“…cortisol and prolactin). Van Cutsem et al (2017) have shown that performing 45-minute of the Stroop task and an endurance task increases the concentration of cortisol (a physiological index of mental fatigue) [16]. Carrasco Páez et al (2007) also reported that prolactin secretion, known as a central fatigue index in the blood [17], is also affected by psychological and physical stress [18].…”
Section: The Effects Of Performing Mental Exertion During Cycling Exementioning
confidence: 99%
See 1 more Smart Citation
“…cortisol and prolactin). Van Cutsem et al (2017) have shown that performing 45-minute of the Stroop task and an endurance task increases the concentration of cortisol (a physiological index of mental fatigue) [16]. Carrasco Páez et al (2007) also reported that prolactin secretion, known as a central fatigue index in the blood [17], is also affected by psychological and physical stress [18].…”
Section: The Effects Of Performing Mental Exertion During Cycling Exementioning
confidence: 99%
“…Following these instructions, participants started cycling at 80 W for 3 min, and thereafter resistance was increased by 40 W every 3 min, until exhaustion (defined as a cadence of less than 60 revolutions per minute (RPM) for more than 5 s despite strong verbal encouragement). The W max (i.e peak power output (PPO)) was calculated with the formula: W max = W out + (t/180) × 40 [W out : workload of the last completed stage; t: time (seconds) in the final stage] [16].…”
Section: Maximal Cycling Exercise Protocolmentioning
confidence: 99%
“…Many studies have shown that the brain plays a key role in the establishment of fatigue and, therefore, exercise performance [6][7][8][9]. In this regard, several centrally-acting performance modifiers have been shown to influence exercise performance [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mental fatigue might be not so bad for exercise performance after all: a systematic review and bias-sensitive meta-analysis. last few years, with some studies replicating Marcora et al's (2009) findings (e.g., Head et al, 2016;MacMahon, Schücker, Hagemann, & Strauss, 2014;Pires et al, 2018) and others reporting null effects (Holgado, Troya, Perales, Vadillo, & Sanabria, 2020;Silva-Cavalcante et al, 2018;Van Cutsem, De Pauw, et al, 2017). This discrepancy could be accounted for several factors that deserve closer examination.…”
Section: Introductionmentioning
confidence: 99%